World-wide trends in sandy shoreline changes during the past century - Bird, Eric (Géographie physique et Quaternaire, 1981)
According to most specialists, during the past century, erosion has been prevalent on sandy shorelines around the World, while sectors of continuing progradation are very restricted. On the world scale the assumption that erosion on some sectors of sandy shorelines is balanced by deposition on other sectors has been shown to be incorrect. A brief analysis of the situation is made. Sectors of sandy shorelines that have advanced during the past century fall into one of the nine categories defined. In addition, nine factors are discussed in regard to sandy shoreline erosion. It is concluded that there is no single explanation to account for the modern prevalence of erosion on the world's sandy shorelines. Further investigations are needed to understand properly both the patterns and rates of changes on sandy shorelines.